MSMEs GROWTH IN UTTAR PRADESH DURING PRE AND POST COVID-19 PERIODS: LESSONS FOR SUSTAINABLE SOCIO-ECONOMIC GROWTH - Akansha Gupta; Rani, Manju (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The surge in the number of Micro, Small, and Medium Enterprises (MSMEs) in India and their substantial contributions to the nation's development is noteworthy. MSMEs serve as pivotal growth drivers for the Indian economy, fostering innovation, facilitating exports, and nurturing a dynamic entrepreneurial ecosystem. Currently, Maharashtra leads with the highest count of MSMEs, followed by Tamil Nadu and Uttar Pradesh. Uttar Pradesh, ranking as the third-largest economy in India and contributing 8% to the national GDP, serves as a significant economic pillar. Notably, the MSME sector, standing as the second-largest employer following agriculture, endured the most significant impact of the COVID-19 pandemic. This study aims to analyse the trajectory of MSME growth, both in terms of numbers and employment, in Uttar Pradesh from 2015-16 to 2022-23, considering the pre and post-COVID-19 landscape.